Traces of the History of the Composer's Role: Development of Deli Malay Music - Lukitaningsih, Lukitaningsih; Priyatna, Ajeng Silvi; Ayubi, Muhammad Ali; Simbolon, Kartika Sarma; Aritonang, Mona Natalia; Wati, Rahma (Gondang: Jurnal Seni dan Budaya, 2024)
This article describes the role of composers in the development of Deli Malay music in the city of Medan and examines the development of Deli Malay music from a scientific perspective history. The purpose of this study is to analyze the historical traces of the role of composers in Deli Malay music and elaborate on the development of Deli Malay music in the city of Medan. The method used here is a historical method with a literature study for data collection. The results of the research on Malay music show a combination with Arabic music based on Islamic Sharia, as found in the instruments and musical arrangements adapted to Malay-style characteristics, the song lyrics contains poems about daily life, full of moral messages, and have an influence on the Malay community as well as on other ethnic groups, especially in Medan city. Malay music reached its peak in the 1970s, signified by the many Malay orchestras that grew and developed during that time. By the year 2000, Malay music had experienced technological advances in terms of musical instruments, making Malay music treasures more colorful, less rigid, and more varied, providing a new atmosphere in Malay music. The role of musical composers is important in the development and maintenance of Malay Deli's musical heritage. They are responsible for creating new songs, arranging traditional music, and preserving the existing music repertoire. Thus, the role of Deli Malay music composers is crucial in ensuring the continuity and development of traditional music, keeping this cultural heritage alive and relevant amid changing times.